Faktor-Faktor yang Memengaruhi Keputusan Transfer Pricing yang diambil oleh Perusahaan - Putri, Sari Yuli; Bayu, Septian (Jurnal Akuntansi, 2024)
Transfer  pricing  refers  to  the  price  set  by  parties  with  special  relationships  when  conducting  transactions  with  each  other.  Examples  of  such  transactions  include  the  provision  of  management  services,  distribution  of  goods,  and  lending.  Companies  often  use  transfer  pricing  practices  to  manage  their  tax  obligations.  The  purpose  of  this  study  is  to  identify  the  factors  that  influence  companies'  decisions  in  implementing  transfer  pricing.  Several  independent  variables  examined  in  this  study  include  tax  burden,  foreign  ownership,  and  foreign  exchange  rates.  Meanwhile,  the  dependent  variable  in  this  study  is  transfer  pricing,  which  is  measured  through  the  volume  of  sales  to  related  parties.  Multiple  linear  regression  analysis  method  is  used  in  this  study  using  SPSS  23  software.  The  research  findings  indicate  that  the  significant  variable  in  companies'  decision  to  implement  transfer  pricing  practices  is  foreign  ownership.  However,  tax  burden  and  foreign  exchange  rates  do  not  have  a  significant  influence  on  companies'  decisions  in  implementing  transfer  pricing. Keywords:  transfer pricing,  tax burden,  foreign ownership,  exchange rate